2017
DOI: 10.7717/peerj.3938
|View full text |Cite
|
Sign up to set email alerts
|

Inferring microevolution from museum collections and resampling: lessons learned fromCepaea

Abstract: Natural history collections are an important and largely untapped source of long-term data on evolutionary changes in wild populations. Here, we utilize three large geo-referenced sets of samples of the common European land-snail Cepaea nemoralis stored in the collection of Naturalis Biodiversity Center in Leiden, the Netherlands. Resampling of these populations allowed us to gain insight into changes occurring over 95, 69, and 50 years. Cepaea nemoralis is polymorphic for the colour and banding of the shell; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In C. nemoralis , lighter‐colored shells absorb less heat and allow snails to maintain a lower body temperature (Heath, 1975) and higher water content (Chang, 1991). Many studies have shown that lighter (vs. darker) snails have a selective advantage in hotter/sunnier (vs. colder/shaded) environments, whether one looks at continental‐scale latitudinal clines (Jones et al, 1977; Silvertown et al, 2011), local‐scale habitat comparisons (Kerstes et al, 2019; Ozgo & Kinnison, 2008; Schilthuizen, 2013), or historical comparisons in the context of climate change (Ożgo et al, 2017; Ożgo & Schilthuizen, 2012). Local variations in morph frequencies have also been linked to predation pressure, generally in the context of visual selection (frequency‐dependent selection and/or crypsis; Jones et al, 1977; Surmacki et al, 2013, and references therein; but see Cook, 2008), but morph differences in shell resistance to crushing have also been described (Rosin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In C. nemoralis , lighter‐colored shells absorb less heat and allow snails to maintain a lower body temperature (Heath, 1975) and higher water content (Chang, 1991). Many studies have shown that lighter (vs. darker) snails have a selective advantage in hotter/sunnier (vs. colder/shaded) environments, whether one looks at continental‐scale latitudinal clines (Jones et al, 1977; Silvertown et al, 2011), local‐scale habitat comparisons (Kerstes et al, 2019; Ozgo & Kinnison, 2008; Schilthuizen, 2013), or historical comparisons in the context of climate change (Ożgo et al, 2017; Ożgo & Schilthuizen, 2012). Local variations in morph frequencies have also been linked to predation pressure, generally in the context of visual selection (frequency‐dependent selection and/or crypsis; Jones et al, 1977; Surmacki et al, 2013, and references therein; but see Cook, 2008), but morph differences in shell resistance to crushing have also been described (Rosin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In C. nemoralis , lighter colored shells absorb less heat and allow snails to maintain a lower body temperature (Heath, 1975) and higher water content (Chang, 1991). Many studies have shown that lighter (darker) snails are as a consequence selectively advantaged in hotter/sunnier (colder/shaded) environments, whether one looks at continental-scale latitudinal clines (Jones et al, 1977; Silvertown et al, 2011), local-scale habitat comparisons (Kerstes, Breeschoten, Kalkman, & Schilthuizen, 2019; Ozgo & Kinnison, 2008; Schilthuizen, 2013), or historical comparisons in the context of climate change (Ożgo, Liew, Webster, & Schilthuizen, 2017; Ożgo & Schilthuizen, 2012). Local variations in morph frequencies have also been tied to predation pressure, with both frequency-dependent and crypsis-based visual selection thought to play a role (Jones et al, 1977; Surmacki, Ożarowska-Nowicka, & Rosin, 2013, and references therein; but see Cook, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Cepaea , we now have some understanding of the pigments and shell proteome (Mann and Jackson 2014; Williams 2017), and have begun to use new genomic methods to identify the genes involved (Kerkvliet et al 2017; Richards et al 2013). However, while ongoing studies on these animals continue to provide evidence for the relative role of various forms of natural selection and random drift in promoting and maintaining variation (Cameron and Cook 2012; Cameron et al 2013; Cook 2014; Cook et al 1999; Davison and Clarke 2000; Ożgo et al 2017; Ożgo and Schilthuizen 2012; Schilthuizen 2013; Silvertown et al 2011), progress in understanding the patterns of shell variation in Cepaea has largely stalled since the 1970s.…”
Section: Introductionmentioning
confidence: 99%